The Quality of Education and the Process of Non-Cognitive Skills Cultivation in Côte d’Ivoire: Focusing on self-efficacy formed by schooling and apprenticeship - Komatsu, Yuki (Africa Educational Research Journal, 2024)
The purpose of this study is to clarify the process of children's self-efficacy cultivation in Côte d’Ivoire, focusing on schooling and apprenticeship. The field research suggested that in the context of schooling, pupil-teacher interaction in primary education contribute to the self-efficacy cultivation. In addition, apprenticeship in the informal sector during long vacations showed the process of self-efficacy cultivation by depicting one boy's relationship with his master, who was marginalized from schooling. In conclusion, the quality of education in Côte d’Ivoire was examined from the perspective of non-cognitive skills, pointing out the multilayered disparities in the quality of education inherent in classrooms and the exclusion of pupils with learning difficulties within the institutional framework of schooling. However, such pupils do not continue to be excluded outside of school. They are included in a society in which the quality of cognitive and non-cognitive education is mutually complementary between schooling and apprenticeship.